2016
DOI: 10.1038/srep28042
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteomic analysis of stable coronary artery disease indicates impairment of reverse cholesterol pathway

Abstract: Coronary artery disease (CAD) is one of the largest causes of death worldwide yet the traditional risk factors, although useful in identifying people at high risk, lack the desired predictive accuracy. Techniques like quantitative plasma proteomics holds immense potential to identify newer markers and this study (conducted in three phases) was aimed to identify differentially expressed proteins in stable CAD patients. In the first (discovery) phase, plasma from CAD cases (angiographically proven) and controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…The data obtained highlight peculiar characteristics of patients having higher residual cardiovascular risk due to higher levels of Apo C‐III. In particular, our findings demonstrated that there is a strong relationship among Apos which are under expressed in patients with low level of Apo C‐III, thus confirming the involvement of cholesterol efflux as already demonstrated by Basak et al …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The data obtained highlight peculiar characteristics of patients having higher residual cardiovascular risk due to higher levels of Apo C‐III. In particular, our findings demonstrated that there is a strong relationship among Apos which are under expressed in patients with low level of Apo C‐III, thus confirming the involvement of cholesterol efflux as already demonstrated by Basak et al …”
Section: Discussionsupporting
confidence: 90%
“…The plasma proteome of CAD patients has been widely studied: the expression of plasma proteins of CAD patients was studied against healthy non‐CAD controls and patients with acute coronary syndrome were compared to stable patients . Several studies also demonstrated that urinary peptide biomarkers reflect atherosclerosis in mice and humans .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple protein changes have been also reported to date in plasma. These studies, involving use of both gel-based and non-gel-based techniques (reviewed in [ 20 ]), addressed the identification of features associated with specific CVD phenotypes, including abdominal aneurism progression [ 21 ]; fibrin clot-bound proteins in acute myocardial infarction [ 22 ]; stable coronary artery disease pathophysiology [ 23 ]; prognostic biomarkers in peripheral arterial occlusive disease [ 24 ]; venous thromboembolism risk prediction [ 25 ]; and extracellular matrix remodeling in hypertrophic cardiomyopathy [ 26 ]. Significant changes in multiple proteins included various forms of apoliproteins [ 23 ]; thrombospondin 1 [ 10 ]; alpha 2 macroglobulin [ 10 ]; transthyretin [ 24 ]; complement factor B [ 24 ]; platelet-derived growth factor β [ 25 ]; and fibronectin [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…its prolonged treatment lowers the levels of pyruvate and inhibits glucose induced ATP production in pancreatic cells 53 55 . Also, in a case control study in the Indian population, we have previously shown that high levels of cysteine is associated with cardiovascular disease 32 , and interestingly total proteins in CAD patients was shown to be significantly lower as compared to control groups 56 . Interestingly, high leucine diet has been proposed to be helpful in attenuating heart diseases 57 .…”
Section: Cysteine and Pyruvate Relationmentioning
confidence: 93%